Multistage Selection and the Financing of New Ventures - Eckhardt, Jonathan T.; Shane, Scott; Delmar, Frédéric (Management Science, 2006)
Using a random sample of 221 new Swedish ventures initiated in 1998, we examine why some new ventures are more likely than others to successfully be awarded capital from external sources. We examine venture financing as a staged selection process in which two sequential selection events systematically winnow the population of ventures and influence which ventures receive financing. For a venture to receive external financing its founders must first select it as a candidate for external funding, and then a financier must fund it. We find evidence that founders select ventures as candidates for external finance based on their perceptions of market competition, market growth, and employment growth, while financiers base funding decisions on objective verifiable indicators of venture development, such as the completion of organizing activities, marketing activities, and the level of sales of the venture. Our findings have implications for venture financing and evolutionary theories of social processes.